2021
DOI: 10.1007/s11356-021-16070-z
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of oxidative stress by trans-Anethole via modulating phase I and phase II enzymes against hepatic damage induced by CCl4 in male Wistar rats

Abstract: The current study was designed to assess the in vivo hepatoprotective properties of trans-Anethole and it is a principal aromatic component of star anise possessed several therapeutic properties. Results showed that CCl 4 treatment elevated the levels of different serum markers like serum glutamate oxaloacetate transaminase (SGOT) by 4.74 fold, serum glutamate pyruvate transaminase (SGPT) by 3.47 fold, aspartate alkaline phosphatase (ALP) by 3.55 fold, direct bilirubin by 3.48 fold and total bilirubin by 2.38 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…25 The range of serum ALT is approximately 26.45−63.93 U/L, and the range of serum AST is approximately 62.83−153.23 U/L in Wistar rats. 26 The results of serum AST and ALT levels of the rats in the CRS group were higher than the normal range. The H&E staining indicated that the liver histological structure of CRS rats was impaired, and the hepatic lobule structure was unclear.…”
Section: ■ Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…25 The range of serum ALT is approximately 26.45−63.93 U/L, and the range of serum AST is approximately 62.83−153.23 U/L in Wistar rats. 26 The results of serum AST and ALT levels of the rats in the CRS group were higher than the normal range. The H&E staining indicated that the liver histological structure of CRS rats was impaired, and the hepatic lobule structure was unclear.…”
Section: ■ Discussionmentioning
confidence: 82%
“…Traditional markers AST and ALT are commonly used to detect liver diseases . The range of serum ALT is approximately 26.45–63.93 U/L, and the range of serum AST is approximately 62.83–153.23 U/L in Wistar rats . The results of serum AST and ALT levels of the rats in the CRS group were higher than the normal range.…”
Section: Discussionmentioning
confidence: 97%
“…Total protein mainly consists of albumin and globulin, and their ratio indicates protein metabolism and immune function ( Stohl et al, 2019 ; Yoshino et al, 2019 ). Blood ALT, AST, and ALP are usually used to evaluate the degree of liver oxidative damage, and their decreased activity is indicative of an improved redox status ( Dalia et al, 2017 ; Pandit et al, 2022 ). LDH and CK mainly exist in cardiomyocytes and can be released when cardiomyocytes are damaged.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature was not controlled during the last 24 days, and very rare amount of extreme cold or hot weather during April could be stress for broilers as heat stress resulted in decrease in ADG, ADFI, and FGR (Chang et al, 2020; Zhang et al, 2017). Serum AST and ALT are commonly used as indexes to evaluate the damage degree of liver (Pandit et al, 2021). Compared with control group, heat stress reduced liver weight and increased serum AST levels of broiler (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%